Does marketization promote economic growth?—Empirical evidence from 26 transition countries - Qiang Wang; Qi Gao (Humanities & Social Sciences Communications)
Abstract With the market as an important means of allocating resources, marketization reforms are important for promoting economic growth in developing countries. This paper empirically analyses the relationship between the level of marketization and economic growth via panel data of 26 transition countries over the period of 1995–2022. The results show that an increase in the level of marketization has a heterogeneous effect on economic growth in transition countries. Instead, the increase in economic freedom weakens the contribution of labor and capital inputs to economic growth. A deviation of a country’s index of economic freedom from the optimal level of marketization can result in a loss of efficiency in resource allocation. This finding suggests that the promotion mechanism of economic growth by an increase in the level of marketization is constrained by many factors in a country. Therefore, developing countries should pay attention to the market failure caused by the conflict between formal and informal systems in the process of promoting market-oriented reforms. While nonmarket approaches can address market failures, they may also lag behind the needs of economic development. Developing countries should promote market-oriented reforms in light of their own realities and pay attention to the areas and pace of market-oriented reforms.